Studi atas Akuntansi Universitas sebagai Organisasi Nirlaba: Menuju Good University Governance - Ely Windarti Hastuti (University of Darussalam Gontor, 2015)
As one of the non-profit organizations, the College became one of the entities of interest to be discussed, because it may just be a rarity that write about the institution of this one. In PSAK 45 published Bond Akuntan Indonesia (2010) submitted thatthe characteristics of different non-profit entities with business entities. The fundamental difference lies in the way the non-profit entity acquiring the resources neededto perform a variety of activities. As one of the non-profit organizations, the Collegebecame one of the entities of interest to be discussed, because it may just be a rarity that write about the institution of this one. Higher education institutions have long experienced the pendikotomian into the universities, private colleges and non-governmental and non-profit organization. Therefore, this paper tries to discuss about the treatment of accounting for the University as one of the non-profit organizations in order to achieve transparency and accountability towards the public, be it government-owned universities, or private and toward a new concept of the currently vigorous proclaimed, i.e. Good University Governance.